PROSEDUR PENAGIHAN TERMIN PROYEK PADA PT PETRA PENIDA ENERGI INDONESIA - Jihan Windi Adila (2023)
Project term billing is billing for payment of work progress that has been completed. Term billing can be a benchmark for work progress, because it can only be done if the work progress is appropriate, so that the project can be completed on time and operational costs become more effective. The purpose of this writing is to find out the procedures and supporting documents in project term billing, as well as recording of term disbursements at PT Petra Penida Energi Indonesia. In writing, the data and information obtained at the data collection stage are then processed using a qualitative descriptive method. The project term billing procedure begins with completing the contract administration and personnel, then obtaining a work start order stating that the project can start work. When the progress of project completion is by the billing requirements, a monthly project report will be made and other documents such as payment request letters, receipts, tax invoices, absolute liability letters, work handover minutes, work inspection minutes, and payment minutes will be submitted to the client for processing thebilling. If successful, the client provides a disbursement order and the disbursement of the term will be recorded in the project financial statements.